Jointly Optimal Taxes for Different Types of Income - Johannes Hermle; Andreas Peichl (Center for Economic Studies and ifo Institute (CESifo), 2018)
We develop and estimate a model of jointly optimal income taxes for different types of income. Compared to standard optimal tax formulas, optimal schedular income tax rates additionally depend on cross-elasticities between tax bases capturing fiscal externalities. We discuss two applications: the taxation of different income sources such as labor or capital income and the taxation of couples. For these applications, we calculate income type-specific optimal tax rates for Germany using rich panel data from administrative tax records. We first estimate income-type specific elasticities with respect to the next-of-tax rate and show that responses to taxes differ substantially by income source and by gender. Second, we calculate social welfare weights implicit in the German personal income tax schedule which again differ between income sources and by gender. Using these estimates, we consider a tax simplification reform by calculating optimal schedular linear income tax rates. We find that optimal tax rates are significantly lower for labor income than for self-employment and capital income as well as for married women than men.
Keywords: H21; H24; H26; D60; 330; optimal taxation; income types; marginal social welfare weights; flat tax; administrative data